Children and Their Parents: A Review of Fertility and Causality - Clarke, D (Blackwell Publishing Ltd, 2018)
Childbearing decisions are not made in isolation. They are taken in concert with decisions regarding work, marriage, health investments and stocks, as well as many other observable and non-observable considerations. Drawing causal inferences regarding the effect of additional children on family outcomes is complicated by these endogenous factors. This paper lays out the issues involved in estimating the effect of additional child births on family outcomes, and the assumptions underlying the range of estimators and methodologies proposed in the economic literature. The common pitfalls of these estimators are discussed, as well as their potential to bias our interpretation of the effect additional births have on children and parents, both in the existing literature and in future work in the face of changing patterns of childbearing and child-rearing. © 2017 John Wiley & Sons Ltd.